CRIMINAL RESPONSIBILITY FOR PERPETRATORS OF THE CRIMINAL ACT OF EMBAGLEY OF RENTAL CARS IN CONNECTION WITH ARTICLE 372 OF THE CRIMINAL CODE (Case Study at Wulan Rent Car) - Patul Mudin, Arip; Guntara, Deny; Abas, Muhamad (Jurnal Ilmiah Advokasi, 2025)
Every criminal act cannot be separated from a series of causes and effects. Legal events that conflict with statutory regulations always cause harm to other people. Criminal accountability is intended to determine the condition of a perpetrator of a criminal act, whether or not the perpetrator can be punished for the criminal act he committed, in this case namely the crime of embezzlement as regulated in Article 372 of the Criminal Code. The issues raised are  What is the criminal responsibility for the perpetrator of the criminal act of embezzling a rental car belonging to Wulan Rent Car and what criminal sanctions are applied to the perpetrator of the criminal act of embezzling a rental car belonging to Wulan Rent Car. The research method used is qualitative using an empirical juridical approach because it examines actual legal events directly. Criminal responsibility is fundamental for compensating for losses incurred by victims of criminal acts of embezzlement, namely by being accountable before the law by bearing the legal consequences that they must undergo because this is within the authority of law enforcement officials and compensating for losses suffered by victims of criminal acts of embezzlement. victims of criminal acts worth of lost objects. determined. Settlement of compensation must also be carried out through a court decision in the criminal field which has permanent legal force.Keywords: Criminal Liability, Crime, Embezzlement.